Воздействие рецепторного антагониста IL-1 на нейрогенные факторы воспаления при черепно-мозговой травме - Shanin, S. N.; Filatenkova, T. A.; Fomicheva, E. E.; Serebryanaya, N. B. (Патогенез, 2022)
Тезисы конференции